1996
DOI: 10.1210/endo.137.5.8612544
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of different populations of bone cells to mechanical stress.

Abstract: To explore lineage-dependent responses to mechanical stress in bone cells, newborn rat calvarial cells, exhibiting differential characteristics of osteoblastic and osteocytic cells, were compared in their immediate and late responses to stretching. Seven fractions of sequentially prepared cells were cultured on Matrigel to promote their differentiation. By cyclically stretching the flexible bottom of culture plates, cells were exposed to a physiological stress of approximately 4000 microstrain on Matrigel. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 22 publications
1
46
0
1
Order By: Relevance
“…This result indicates that osteocytes are more sensitive than endothelial cells, in which 20% elongation on silicon membrane caused little change in [Ca 2ϩ ] i (39). Osteocytes appear to be extremely sensitive to mechanical strain since our previous study of anabolic reaction showed that young osteocytes respond to low levels of mechanical strain (up to 4,000 E) to which osteoblasts do not respond (5). It is quite likely that the development of extensive cell processes, which is accompanied by differentiation of osteocytes, allows these cells to acquire sensitivity to stretching by the SA-Cat concentrated along the processes, as we presented in this article.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This result indicates that osteocytes are more sensitive than endothelial cells, in which 20% elongation on silicon membrane caused little change in [Ca 2ϩ ] i (39). Osteocytes appear to be extremely sensitive to mechanical strain since our previous study of anabolic reaction showed that young osteocytes respond to low levels of mechanical strain (up to 4,000 E) to which osteoblasts do not respond (5). It is quite likely that the development of extensive cell processes, which is accompanied by differentiation of osteocytes, allows these cells to acquire sensitivity to stretching by the SA-Cat concentrated along the processes, as we presented in this article.…”
Section: Discussionmentioning
confidence: 57%
“…Rat Osteocytes-Rat osteocytes were prepared from frontal and parietal bones that were dissected aseptically from newborn rats according to the method of Mikuni-Takagaki et al (5) with some modifications. Briefly, pieces of bone were stripped of periosteal soft tissue and sutures and digested with 25 ml of 0.75 mg/ml collagenase.…”
Section: Osteocytes Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Osteoblasts and osteocytes differ in their sensitivity to FSS or stretching and demonstrate different kinetics of ␤-catenin nuclear translocation, but both cell types respond to mechanical stimulation with an increase in intracellular calcium and NO production (53)(54)(55)(56)(57). Nuclear ␤-catenin together with its binding partner Lef1 regulates genes in osteoblasts and osteocytes necessary for maintenance of normal bone mass in vivo, including cox-2, and control osteoblast as well as osteoclast differentiation and survival (27-30, 41, 58).…”
Section: Discussionmentioning
confidence: 99%